Imaging in gynecological disease (20): clinical and ultrasound characteristics of adnexal torsion. (10th November 2020) - Moro, F.; Bolomini, G.; Sibal, M.; Vijayaraghavan, S. B.; Venkatesh, P.; Nardelli, F.; Pasciuto, T.; Mascilini, F.; Pozzati, F.; Leone, F. P. G.; Josefsson, H.; Epstein, E.; et al.
ABSTRACT: Objectives: To describe the clinical and ultrasound characteristics of adnexal torsion. Methods: This was a retrospective study. From the operative records of the eight participating gynecological ultrasound centers, we identified patients with a surgically confirmed diagnosis of adnexal torsion, defined as surgical evidence of ovarian pedicle, paraovarian cyst and/or Fallopian tube twisted on its own axis, who had undergone preoperative ultrasound examination by an experienced examiner, between 2008 and 2018. Only cases with at least two available ultrasound images and/or videoclips (one grayscale and one with Doppler evaluation) were included. Clinical, ultrasound, surgical and histological information was retrieved from each patient's medical record and entered into an Excel file by the principal investigator at each center. In addition, two authors reviewed all available ultrasound images and videoclips of the twisted adnexa, with regard to the presence of four predefined ultrasound features reported to be characteristic of adnexal torsion: (1) ovarian stromal edema with or without peripherally displaced antral follicles, (2) the follicular ring sign, (3) the whirlpool sign and (4) absence of vascularization in the twisted organ. Results: A total of 315 cases of adnexal torsion were identified. The median age of the patients was 30 (range, 1–88) years. Most patients were premenopausal (284/314; 90.4%) and presented with acute or subacute pelvic pain (305/315; 96.8%). The surgical approach was laparoscopic in 239/312 (76.6%) patients and conservative surgery (untwisting with or without excision of a lesion) was performed in 149/315 (47.3%) cases. According to the original ultrasound reports, the median largest diameter of the twisted organ was 83 (range, 30–349) mm. Free fluid in the pouch of Douglas was detected in 196/275 (71.3%) patients. Ovarian stromal edema with or without peripherally displaced antral follicles was reported in the original ultrasound report in 167/241 (69.3%) patients, the whirlpool sign in 178/226 (78.8%) patients, absent color Doppler signals in the twisted organ in 119/269 (44.2%) patients and the follicular ring sign in 51/134 (38.1%) patients. On retrospective review of images and videoclips, ovarian stromal edema with or without peripherally displaced antral follicles (201/254; 79.1%) and the whirlpool sign (139/153; 90.8%) were the most commonly detected features of adnexal torsion. Conclusion: Most patients with surgically confirmed adnexal torsion are of reproductive age and present with acute or subacute pain. Common ultrasound signs are an enlarged adnexa, the whirlpool sign, ovarian stromal edema with or without peripherally displaced antral follicles and free fluid in the pelvis. The follicular ring sign and absence of Doppler signals in the twisted organ are slightly less common signs. Recognizing ultrasound signs of adnexal torsion is important so that the correct treatment, i.e. surgery without delay, can be offered. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.